The moon as my witness. (1st October 2015) - Allen, Jess; Preece, Bronwyn
Full:new was a transnational score for a site-based Authentic Movement (AM) and ecopoetic writing practice, performed for the duration of a complete lunar phase: two women (one in Wales, the other in Canada) moving/writing authentically on their respective sites for 28 minutes every day, for 28 consecutive days. The process led to the creation of a collaborative, concrete poem: the length of each line waxing and waning daily with the moon. In an adaptation of the 'classic' form of AM, the moverwitness dyad was stretched into a virtual arc across the northern hemisphere, held within the witnessing circle of the moon's cycle: 'witnessing' thus took the form of a remote, reciprocal commitment to self, site and other, through a strict adherence to the score. In these artist pages, we offer a reflective poetic-photographic documentation of this practice, with an accompanying written commentary on the role of AM within this process: how can the authentically moving body, transnationally witnessed, become a resonant organ both for sensing ecological relations and writing them into being?